CHALLENGES IN AUTOMOBILE INDUSTRY IN INDIA IN THE AFTERMATH OF COVID-19 - Tejinder Singh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This paper attempts to study the challenges faced by the companies engaged in the automobile business in India post emergence of lockdown conditions imposed due to the spread of novel coronavirus. Since the nature of automobile industry is manufacturing in nature, the damage to the sector is obvious because of halt in production due to lockdown restricting physical movement of people. A statistical comparison between the automobile index and Nifty 50 index has also been done.